The Relationship Between Body Mass Index and Menstrual Cycle in Female Students at MTs Pamulangan Jetis Yogyakarta - Daryanti Menik Sri; Saniatur Rizki (Midwifery Care Journal, 2026)
One of the common problems faced by adolescents worldwide is menstrual cycle disorders. This disorder can manifest itself as variations in cycle duration, which can impact long-term reproductive health. One contributing factor to menstrual irregularities is body mass index, as active fat tissue affects the balance of reproductive hormones, particularly estrogen and progesterone. The purpose of this study is to determine the correlation between BMI and the menstrual cycle. This study employed a correlational approach with a quantitative design and cross-sectional method. A sample of 65 women was selected using purposive sampling, and the samples were selected based on specific criteria. Data were collected through height and weight measurements and questionnaires. The data were analyzed using Fisher's exact test. The results showed a p-value of 0.000, less than 0.05, with a correlation level of 0.541, which is considered sufficient. This indicates a relationship between BMI and the menstrual cycle. This research is expected to improve students' understanding of the importance of maintaining a healthy diet and daily nutritional needs.